Survival results according to Oncotype Dx recurrence score in patients with hormone receptor positive HER-2 negative early-stage breast cancer: first multicenter Oncotype Dx recurrence score survival data of Turkey - Ünal, Çağlar; Özmen, Tolga; Ordu, Çetin; Pilanci, Kezban Nur; İlgün, Ahmet Serkan; Gökmen, Erhan; Almuradova, Elvina; Özdoğan, Mustafa; Güler, Nilüfer; Uras, Cihan; Kara, Halil; Demircan, Orhan; et al. (Frontiers in Oncology, 2023)
Background The Oncotype Dx risk score (ODx-RS) guides the adjuvant chemotherapy decision-making process for patients with early-stage hormone receptor-positive, HER-2 receptor-negative breast cancer. This study aimed to evaluate survival and its correlation with ODx-RS in pT1-2, N0-N1mic patients treated with adjuvant therapy based on tumor board decisions. Patients and Methods Estrogen-positive HER-2 negative early-stage breast cancer patients (pT1-2 N0, N1mic) with known ODx-RS, operated on between 2010 and 2014, were included in this study. The primary endpoint was to evaluate disease-free survival (DFS) rates according to ODx-RS. Results A total of 203 eligible patients were included in the study, with a median age of 48 (range 26-75) and median follow-up of 84 (range 23-138) months. ROC curve analysis for all patients revealed a recurrence cut-off age of 45 years, prompting evaluation by grouping patients as ≤45 years vs. >45 years. No significant difference in five-year DFS rates was observed between the endocrine-only (ET) and chemo-endocrine (CE) groups. However, among the ET group, DFS was higher in patients over 45 years compared to those aged ≤45 years. When stratifying by ODx-RS as 0-17 and ≥18, DFS was significantly higher in the former group within the ET group. However, such differences were not seen in the CE group. In the ET group, an ODx-RS ≥18 and menopausal status were identified as independent factors affecting survival, with only an ODx-RS ≥18 impacting DFS in patients aged ≤45 years. The ROC curve analysis for this subgroup found the ODx-RS cut-off to be 18. Conclusion This first multicenter Oncotype Dx survival analysis in Turkey demonstrates the importance of Oncotype Dx recurrence score and age in determining treatment strategies for early-stage breast cancer patients. Our findings suggest that the addition of chemotherapy to endocrine therapy in young patients (≤45 years) with Oncotype Dx recurrence scores of ≥18 improves DFS.